Dick Tracy - Taylor, Ray, 1888-1952; James, Alan, 1890-1952; Byrd, Ralph, 1909-1952; Republic Pictures Corporation; Cinetel Films ([Los Angeles, CA] : Republic Pictures Corp., 1937)
Tracy tries to find his kidnapped brother as he faces the fiend "Spider."
Part 1: Episode 1 The Spider Strikes ; Episode 2 The Bridge Of Terror ; Episode 3 The Fur Pirates ; Episode 4 Death Rides In The Sky ; Episode 5 Brother Against Brother -- Part 2: Episode 6 Dangerous Waters ; Episode 7 The Ghost Town Mystery ; Episode 8 Battle In The Clouds ; Episode 9 The Stratosphere Adventure ; Episode 10 The Gold Ship -- Part 3: Episode 11 Harbor Pursuit ; Episode 12 The Trail Of The Spider ; Episode 13 The Fire Trap ; Episode 14 The Devil In White ; Episode 15 Brothers United.
Based on the cartoon strip by Chester Gould.
Ralph Byrd, Kay Hughes, Smiley Burnette, Lee Van Atta, John Piccori, Carleton Young, Fred Hamilton, Francis X. Bushman.
Photography, William Nobles, Edgar Lyons ; editors, Helene Turner, Edward Todd, Bill Witney.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 7, 2015)
Keywords: Tracy, Dick (Fictitious character) -- Drama; Crime -- United States -- Drama; Brothers -- United States -- Drama; Detective and mystery films; Feature films; Police films; Film serials; Film adaptations; Fiction films; Internet videos; Streaming video